THE EFFECT OF LEADERSHIP AND SUPERVISION ON EMPLOYEE DISCIPLINE AT PT. PERKEBUNAN NUSANTARA III (PERSERO) KEBUN BANDAR SELAMAT - Rahmad Bahagia; Siti Sarah; Linzzy Pratami Putri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
The results of this study have the aim of knowing the existence of "The Influence of Leadership and Supervision on Employee Discipline at PT. Perkebunan Nusantara III (Persero) Kebun Bandar Selamat". The approach taken in this study uses an associative approach. The population in this study were all employees at PT. Perkebunan Nusantara III (Persero) Kebun Bandar Selamat, totaling 264 people with a sample of 72 people using the slovin formula. The data analysis technique uses the Classical Assumption Test, Multiple Linear Regression, Hypothesis Testing (T Test, F Test), & Coefficient of Determination. Data processing in this study using the SPSS 25.00 software program. The data collection technique used a questionnaire technique by producing a positive influence between Leadership on Employee Discipline which could state tcount ttable 4.784 2.972 significant 0.00 0.05. There is a positive influence on employee discipline at PT. Perkebunan Nusantara III (Persero) Kebun Bandar Selamat with tcount 4.784 1,401 ttable significantly.The conclusion of the research on the influence of leadership and supervision on employee discipline at PT. Perkebunan Nusantara III (Persero) Kebun Bandar Selamat states that there is a positive influence, which is based on the results of the Fcount test of 12,984 with a significant value of 0.000 and the value of Ftable 2.391, because Fcount Ftable then Ha rejected.